2021
DOI: 10.3390/cells10081862
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Depletion-Induced Remodeling of Extracellular Matrix and Excitatory Synapses in the Hippocampus of Adult Mice

Abstract: The extracellular matrix (ECM) plays a key role in synaptogenesis and the regulation of synaptic functions in the central nervous system. Recent studies revealed that in addition to dopaminergic and serotoninergic neuromodulatory systems, microglia also contribute to the regulation of ECM remodeling. In the present work, we investigated the physiological role of microglia in the remodeling of perineuronal nets (PNNs), predominantly associated with parvalbumin-immunopositive (PV+) interneurons, and the perisyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 54 publications
(79 reference statements)
5
28
0
Order By: Relevance
“…Upon microglial depletion with PLX5622, we found robust increases in PNN intensity in the PFC, SS Ctx, MO Ctx, and AUD Ctx, but not the CA1 region of the hippocampus, demonstrating that we had sufficient sensitivity to detect further increases in PNN intensity. These findings are supported by a study where microglial elimination with PLX3397 did not alter PNN intensity in the CA1 region 40 .…”
Section: Discussionsupporting
confidence: 72%
“…Upon microglial depletion with PLX5622, we found robust increases in PNN intensity in the PFC, SS Ctx, MO Ctx, and AUD Ctx, but not the CA1 region of the hippocampus, demonstrating that we had sufficient sensitivity to detect further increases in PNN intensity. These findings are supported by a study where microglial elimination with PLX3397 did not alter PNN intensity in the CA1 region 40 .…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, an in vitro study revealed a disruption of perineuronal nets in cultured hippocampal neurons after an incubation with microglia conditioned medium which was accompanied by altered structural synapse numbers and electrophysiological network properties [ 305 ]. In contrast, a depletion of microglia induced more dense perineuronal nets [ 310 ]. As previously introduced, microglia and inflammatory processes are suspected to play an important role in schizophrenia.…”
Section: Interneuron-abnormalities In the Hippocampus Of Schizophreni...mentioning
confidence: 99%
“…Histological analyses have revealed that activated microglia engulf damaged perineuronal nets (PNNs) in the 5xFAD brain, with PNN material identified in both mouse and human microglia [153]. Further, Strackeljan et al [154] observed that the depletion of microglia increased perisynaptic ECM proteoglycan brevican expression, accompanied by elevated expression of presynaptic marker vGluT1 and increased dendritic spine density. Collectively, these studies suggest an interplay between synaptic elements including microglia process tips, the ECM, and key molecules in glia-neuron communication, in regulating structural synaptic plasticity.…”
Section: Factors Influcening the State Of The Penta-partite Synapsementioning
confidence: 99%